(untitled) (International Journal of Engineering and Computer Science, 2016)
In today’s increasingly complex and interconnected world, system-on-a-chip (SoC) performance requirements are influenced by existing as well as evolving and emerging applications. With Moore’s law supplying billions of transistors, and uni-processor architectures delivering diminishing performance, multicore chips are emerging as the prevailing architecture in both general-purpose and application-specific markets. As the core count increases, the need for a scalable on-chip communication fabric that can deliver high bandwidth is gaining in importance, leading to recent multicore chips interconnected with sophisticated on-chip networks. This paper introduces several test logic architectures that facilitate preemptive test scheduling for SoC circuits with embedded deterministic test-based test data compression. The same solutions allow efficient handling of physical constraints in realistic applications. A detailed experimental analysis is carried out on different provisions, architectures and test-related factors to prove the proposed method efficiency over state of methods.